The Effectiveness of Coop-Dis-Q and Literature Circle Strategies in Teaching Reading Comprehension to Students with Different Personalities - Anggara, IGede Arga; Saleh, Mursid; Sofwan, Ahmad (English Education Journal, 2018)
This study investigated the effectiveness of using Coop-Dis-Q (Cooperative-Discussion-Questioning) and Literature Circle strategies in teaching reading comprehension to extrovert and introvert students. 2x2 factorial design of experimental research was carried out to collect the data from 88 eighth grade students of SMP N 1 Kandeman, Batang. Two experimental groups, A and B, were given two different treatments: Coop-Dis-Q and Literature Circle strategies. The result shows that the Ï = 0.00 for both Coop-Dis-Q and Literature Circle strategies in teaching reading comprehension to extrovert and introvert students which verifies the effectiveness of both two strategies. It wa also found that Coop-Dis-Q is more effective than Literature Circle strategy in teaching reading comprehension since the mean value of post test Coop-Dis-Q shows higher score 27.18 and the value of Ï = 0.00. However, the result also shows that there is no difference between extrovert and introvert personalities in teaching reading comprehension since the value of Ï = 0.310. Further, it was found that the Ï of strategy*type value is 0.638 so there is no interaction between teaching reading comprehension strategies and types of personality on the achievement of reading comprehension which proves that personality does not influence studentsâ€™ reading comprehension achievement.